The safety of rapid infusion levetiracetam: A systematic review. Issue 6 (13th May 2022) - Jense, Alexa; Douville, Alyssa; Weiss, Ashley
Abstract: Epilepsy is a common diagnosis and can quickly progress to status epilepticus which requires rapid treatment. Levetiracetam is a frequent treatment choice in these situations. The approved administration of intravenous levetiracetam is an infusion over 15 min. In recent years, studies have been published on faster infusion rates of levetiracetam. The objective of this review is to discuss the safety of levetiracetam as an intravenous push at a rate quicker than recommended. A literature search using PubMed, Cochrane Library, ClinicalTrials.gov, and Google Scholar resulted in 192 articles. Inclusion criteria consisted of English language, human studies, use of levetiracetam administered intravenously at a rate faster than 15 min, discussion of safety, and full‐text availability. After screening, nine articles remained for inclusion. Of the nine articles, one was a prospective, open‐label study, six were retrospective studies, and two were open‐label, randomized controlled trials. The most common rapid infusion speed was 5 min and doses ranged from 280 to 4500 mg. Some of these trials used undiluted levetiracetam and many reported that peripheral access was used for a portion or all of the administrations. There were few adverse effects, including specific adverse effects relating to medication concentration and speed of infusion, in all the studies. Administration of intravenous levetiracetam at a rate faster than recommended in the labeling information appears to be safe and tolerable and can be given via a peripheral line. Rapid infusion of levetiracetam is a beneficial method of administration in an acute care setting where patients need rapid attainment of therapeutic levels of antiepileptic medications. Additional research is needed to ensure that rapid administration of intravenous levetiracetam is as efficacious as the traditional dosing method.